Reposisi Citra melalui Logo Baru Gojek - Iin Soraya; Andi Setyawan (Jurnal Komunikasi, 2020)
This study is entitled "Image Repositioning through the New Gojek Logo", the purpose of this study is to determine the image repositioning through the new Gojek logo, and to find out the logo process in shaping an image for a company. This study uses a constructivist paradigm, the method used in this study is qualitative, the method of analysis uses semiotics. The results of this study are the markers in the new Gojek logo are the outer circle and inner circle logo meaning one button for all. Now Gojek has services that are growing rapidly to 22 services. The ideology contained in this research is SOLVE (separate), that is strength. Ideology solv means that gojek is a strong company. The image reposition contained in this study is that Gojek has begun to position itself as a service company and super-app manager, besides that the round logo is likened to a power button as a meaning as power, namely a company that has great technology. Another meaning as a search symbol (search), in one application Gojek all life access or multifunctional application. Other meanings want to facilitate community life with technology, the button symbol emphasizes that Gojek is a solution in various situations that reflect consumers, partners and merchants contained in one application system.